ANALISIS REGRESI DATA PANEL PADA FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI INDONESIA TAHUN 2015 – 2019 - Mirtawati, Mirtawati; Aulina, Nadiya (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
High rate of poverty in Indonesia is shown by the large number of poor people. This condition means that the economic development is not still be able to increase the walfare of the people. First, we need to analyze which factors that might be able to significantly affect the rates of poverty. The goal of this research is to determine those factors in Indonesia from 2015-2019. Secondary data is used in this research along with Data Panel Regression Analysis that is consisted of time series data in range 2015-2019 and cross section data of 33 provinces in Indonesia that is processed by Eviews 9. The regression model is obtained from Ordinary Least Square estimation through fixed effect model approach using dummy variable to find out different intercept in each provinces which explaining different area. The result show that the economic growth is significantly and negatively affecting the poverty in Indonesia from 2015 to 2019. DKI Jakarta, Riau Islands, and East Kalimantan negatively affected to the factors of poverty while Papua, West Papua, and East Nusa Tenggara positively affected.